2012
DOI: 10.1093/hmg/dds137
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine intake and CYP1A2 variants associated with high caffeine intake protect non-smokers from hypertension

Abstract: The 15q24.1 locus, including CYP1A2, is associated with blood pressure (BP). The CYP1A2 rs762551 C allele is associated with lower CYP1A2 enzyme activity. CYP1A2 metabolizes caffeine and is induced by smoking. The association of caffeine consumption with hypertension remains controversial. We explored the effects of CYP1A2 variants and CYP1A2 enzyme activity on BP, focusing on caffeine as the potential mediator of CYP1A2 effects. Four observational (n = 16 719) and one quasi-experimental studies (n = 106) incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 57 publications
6
35
0
2
Order By: Relevance
“…Such conclusions are partially supported by a study by Guessous et al [58], reporting on the influence of the CYP1A2 gene variants also in relation with the effect of smoking, which is known to induce CYP1A2 [59]. In a combined analysis of 4 observational studies (n = 16,719) and 1 quasi-experimental study (n = 106) including European adults, these authors reported that the mean adjusted SBP and diastolic BP decreased with the number of reported caffeinated cups/day in nonsmokers, but this only occurred among fast metabolizers consuming caffeine.…”
Section: Long-term Risk Of Caffeine On Cardiovascular Eventssupporting
confidence: 61%
“…Such conclusions are partially supported by a study by Guessous et al [58], reporting on the influence of the CYP1A2 gene variants also in relation with the effect of smoking, which is known to induce CYP1A2 [59]. In a combined analysis of 4 observational studies (n = 16,719) and 1 quasi-experimental study (n = 106) including European adults, these authors reported that the mean adjusted SBP and diastolic BP decreased with the number of reported caffeinated cups/day in nonsmokers, but this only occurred among fast metabolizers consuming caffeine.…”
Section: Long-term Risk Of Caffeine On Cardiovascular Eventssupporting
confidence: 61%
“…8 In a crosssectional study, high reported caffeine intake was associated with a lower prevalence of hypertension only in nonsmokers. 9 To date, studies on the association of caffeine and BP have been limited by the use of reported caffeine intake instead of Abstract-Intake of caffeinated beverages might be associated with reduced cardiovascular mortality possibly via the lowering of blood pressure. We estimated the association of ambulatory blood pressure with urinary caffeine and caffeine metabolites in a population-based sample.…”
mentioning
confidence: 99%
“…However, our finding of a significant effect modification from age is limited by the small size of the sample analyzed for age interaction (N = 1676). The modifying effect of smoking was also evaluated by Guessous et al (2012), but inconsistent results were obtained. Furthermore, a significant association of the CYP1A2 rs762551 AA genotype with high caffeine intake, assessed in 5452 subjects from the CoLaus study, was found among non-smokers (N = 4017; OR = 1.83, 95%CI = 1.38-2.45, P < 0.0001) but not in smokers (N = 1435; OR = 1.15, 95%CI = 0.79-1.67, P = 0.77) with evidence for a significant effect modification.…”
Section: Discussionmentioning
confidence: 99%
“…The following papers were excluded: four GWAS (Cornelis et al, 2011;Sulem et al, 2011;Amin et al, 2012;Rodenburg et al, 2012); four studies lacking coffee intake analysis (Sachse et al, 1999;Basvi et al, 2007;Ghotbi et al, 2007;Gunes et al, 2009); eight studies not providing coffee intake data according to rs762551 genotypes (Goodman et al, 2003;Kotsopoulos et al, 2009;Hallström et al, 2010;Schmidt et al, 2010;Guessous et al, 2012;Josse et al, 2012;Palatini et al, 2015;Yamamoto et al, 2015); two studies providing CC and combined AC + AA genotypes counts instead of AA and AC + CC genotype counts (Palatini et al, 2009;Pavanello et al, 2010); two studies using patient samples (Cornelis et al, 2007;Bågeman et al, 2008); and one study with a small sample size . Finally, 12 studies were included in the meta-analysis (Nordmark et al, 2002;Sata et al, 2005;Cornelis et al, 2006;Kotsopoulos et al, 2007;Tan et al, 2007;Jernström et al, 2008;Djordjevic et al, 2010;Popat et al, 2011;Kohno et al, 2013;Lowcock et al, 2013;Tian et al, 2013;Dik et al, 2014) (Figure 1).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%